2017
DOI: 10.26480/icemi.01.2017.139.141
|View full text |Cite
|
Sign up to set email alerts
|

R&D spending value effect research of China’s listed manufacturing companies

Abstract: Through studying the impact of R&D expenditure on the market value of firms according to the data of manufacturinglisted companies in Shanghai and Shenzhen A stock market from 2001 to 2014, we find that the R&D expenditure of manufacturing-listed companies shows a positive correlation with the market value. Meanwhile, R&D expenditure can generate better value effect in smaller firms. The value effect from R&D expenditure in private enterprises is greater than that in state-owned enterprises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…More similar to this paper, some scholars focused on the roles of government subsidies on pharmaceutical innovation. For example, Yin [13] , Czamitzki and Lopesbento [14] , and Zhang, et al [15] respectively confirmed the value of government subsidies in pharmaceutical innovation from the perspectives of promoting innovation investment, reducing R&D risk and improving innovation outputs. Zhang, et al [16] designed the strategic incentive policy for pharmaceutical innovation and shown that such policy can achieve social optimal allocation of pharmaceutical innovation under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 96%
“…More similar to this paper, some scholars focused on the roles of government subsidies on pharmaceutical innovation. For example, Yin [13] , Czamitzki and Lopesbento [14] , and Zhang, et al [15] respectively confirmed the value of government subsidies in pharmaceutical innovation from the perspectives of promoting innovation investment, reducing R&D risk and improving innovation outputs. Zhang, et al [16] designed the strategic incentive policy for pharmaceutical innovation and shown that such policy can achieve social optimal allocation of pharmaceutical innovation under certain conditions.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Kang et al proposed a flexure‐based 6‐DOF parallel nanopositioning stage for precise optics alignment; [ 192 ] the stage with the size of Ф350 × 120 mm 3 achieved the first resonant frequency of 396.1 Hz and the strokes of 4 mm × 4 mm × 4 mm × 4° × 4° × 4° with linear resolution of 15 nm and rotary resolution of 0.14 arcsec. Zhang et al proposed a 6‐DOF micropositioning mechanism for real‐time adjustment of lithography projection lens posture, [ 193 ] which achieved the translation and rotation stroke of more than 50 μm and 200 μrad, respectively. Zhang et al [ 194 ] proposed a novel 6‐DOF micro/nanopositioning system with the characteristics of high resolution, high repeatability, and low parasitic motions, which consisted of three identical limbs including two symmetrical six prismatic–universal–spherical branches; the proposed positioning platform with the size of Ф264 × 148.4 mm 3 achieved the first resonant frequency of 188.84 Hz and the strokes of 80 μm × 80 μm × 60 μm × 400 μrad × 400 μrad ×600 μrad with the linear and rotary resolutions of 5 nm and 100 nrad, respectively.…”
Section: Multi‐dof Piezoelectric Actuationmentioning
confidence: 99%